Identification and characterization of the maltose permease in genetically defined Saccharomyces strain. - Chang, Y S (1989)
Saccharomyces yeasts ferment several alpha-glucosides including maltose, maltotriose, turanose, alpha-methylglucoside, and melezitose. In the utilization of these sugars transport is the rate-limiting step. Several groups of investigators have described the characteristics of the maltose permease (D. E. Kroon and V. V. Koningsberger, Biochim. Biophys. Acta 204:590-609, 1970; R. Serrano, Eur. J. Biochem. 80:97-102, 1977). However, Saccharomyces contains multiple alpha-glucoside transport systems, and these studies have never been performed on a genetically defined strain shown to have only a single permease gene. In this study we isolated maltose-negative mutants in a MAL6 strain and, using a high-resolution mapping technique, we showed that one class of these mutants, the group A mutants, mapped to the MAL61 gene (a member of the MAL6 gene complex). An insertion into the N-terminal-coding region of MAL61 resulted in the constitutive production of MAL61 mRNA and rendered the maltose permease similarly constitutive. Transformation by high-copy-number plasmids containing the MAL61 gene also led to an increase in the maltose permease. A deletion-disruption of MAL61 completely abolished maltose transport activity. Taken together, these results prove that this strain has only a single maltose permease and that this permease is the product of the MAL61 gene. This permease is able to transport maltose and turanose but cannot transport maltotriose, alpha-methylglucoside, or melezitose. The construction of strains with only a single permease will allow us to identify other maltose-inducible transport systems by simple genetic tests and should lead to the identification and characterization of the multiple genes and gene products involved in alpha-glucoside transport in Saccharomyces yeasts.